REVISITING CLASSICAL POLITICAL PHILOSOPHY - Dadhich, Harshita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Republic is one the greatest works of political philosophy. This was precisely Plato’s intent: if the Republic could not alter people’s politics, it could at least alter the lives of those who read it.. It is written in the imperative mood- not by way of an analysis, but rather for warning and counsel. The Republic is in many respects a polemic- directed against current teachers and the practice of contemporary politics. The current teachers against whom it is directed are the younger generation of Sophists. Its purpose is the substitution of a true conception of justice for the false views which common error and sophistic thinking had contrived to spread. Whether he is combating the theory of the sophists, or seeking to reform the actual practice of society, justice is the hinge of Plato’s thought, and the text is his discourse.